PREANALITIČKE GREŠKE U LABORATORIJSKIM UZORCIMA SA ODELJENJA URGENTNE MEDICINE: ISTRAŽIVANJE IZVORA GREŠAKA - Romero, Adolfo; Gómez-Salgado, Juan; Romero-Arana, Adolfo; Gómez-Fernández, José Antonio; Cobos, Andrés; Ramos, María Carmen; Iglesias, María Rosa (Journal of Medical Biochemistry, 2020)
Background: The presence of preanalytical errors is arecurring fact in all areas of healthcare that send samples to laboratories. Increasing the knowledge of possible sources of error in the preanalytical phase has been the objective of this group during the last 10 years. Methods: In this study, descriptive research has been carried out using professionals’ opinions obtained by means of the Strengths, Weaknesses, Opportunities, and Threats method in a focus group. Results: The opinions expressed within the focus group have emphasised the importance of patients’ safety andwillingness for the introduction of a computerized analytical module. The most commented weakness in both hospitals was the transport of samples through the pneumatic tube. Improving the duration of workers’ contracts, especially in the laboratory, and creating a circuit for professional’s localization during the work shift to facilitate potential error solving are some opportunities for the future. Conclusions: Different approaches have been developed depending on the healthcare scenario. For this, establishing a flow of information between the different professionals allows identifying identical aspects through a priori, different points of view. The line to follow is to improve the safety of the patient and also to give professionals an opportunity to express themselves.